Assessing the factors underlying differences in group performance: methodological issues and empirical findings from the highlands of Central Kenya - Place, Frank; Kariuki, Gatarwa; Wangila, Justine; Kristjanson, Patricia; Makauki, Adolf; Ndubi, Jessica (International Food Policy Research Institute, 2002)
This paper examines the performance of rural groups in Kenya and addresses the methodological issues and challenges faced in doing this, and presents the empirical evidence regarding various hypothesized explanatory factors for relative performance levels.... The findings highlight the incredible number, diversity and dynamic nature of groups in the highlands of Kenya (and we suspect this finding is not terribly unique to this region).